Aerodynamic optimization and energy saving of cycling postures for international elite level cyclists - Oggiano, L.; Leirdal, S.; Saetran, L.; Ettema, G. (The Engineering of sport 7, Volume 1, 2008)
Drag in cycling counts for as much as 90% of total resistance opposing motion in a normal time-trial course. A small gain in term of drag reduction can, over a longer time-span (30 - 60 minutes) give a large advantage to the cyclists in terms of power Output saved or velocity gained. The aim of present study was to aerodynamically optimize the cycling posture for each cyclist and thereby improve the athletes' performances. We also wanted to quantify the power Output saving, velocity gains and energy savings of this optimization. Methods: 11 elite cyclists with a maximal aerobic power Output of 481 W were tested at 6 different positions on their time-trial bicycle in a wind tunnel with an air flow at 14.5 m/s. All positions were adjusted frorn their regular position and included both adjustment of seat and handlebar. All cyclists also went through an extensive physiological lest, including lactate threshold and VO2max tests, allowing for individual efficiency calculations at several power Outputs. Results: From the wind tunnel test individual power-output - velocity curves were plotted, showing the effect of the different positions in terms of saved power generation. Showing an average 21.9 W saving in power output and an average of 0.75 km/h gain in velocity at 500 W for the most aerodynamically position. Using each cyclist's efficiency we calculated the theoretical effect of oxygen consumption, Kcal/h and heart rate. Average results show a 0.34 l/min, 101.5 Kcal/h and 14 BPM for the heart, in saving, for the most aerodynamically position. Conclusions: The effect of small adjustments on elite cyclists can have large effect on performance and energy saving. However, care should be taken as the new position can negatively affect power generation and pedaling technique, which might become more energy consuming. Data on this is also collected in present study but needs further analysis.